REFORMA AL … Art. (25.1) DE LA LEY ORGÁNICA DE SERVICIO PÚBLICO, PARA QUE SE SANCIONE AL EMPLEADOR QUE NO GARANTICE EL DERECHO A LA DESCONEXIÓN DIGITAL, SALUD OCUPACIONAL Y ENTREGA DE EQUIPOS, ELEMENTOS E INSUMOS AL SERVIDOR PÚBLICO QUE TELETRABAJA - PALADINES QUIZHPE., ANDREA CECIBEL (2021)
The present thesis constitutes the final report of the research process developed and developed and supported legally in Ecuadorian legislation, which is entitled “REFORMA AL… Art (25.1) OF THE ORGANIC LAW OF PUBLIC SERVICE, TO PUNISH AN EMPLOYER WHO DOES NOT GUARANTEE THE RIGHT TO DIGITAL DISCONNECTION, OCCUPATIONAL HEALTH AND DELIVERY OF EQUIPMENT, ELEMENTS AND SUPPLIES TO THE SERVER PUBLIC WHO TELEWORK “ The purpose is to analyze the importance analyze the importance of the application of administrative sanctions in relation to the violation of rights of the public server, established in the Organic Law of Public Service regarding telework propitiously speak of the Right to Digital Disconnection, Occupational Health and Delivery of equipment, elements and supplies, the same ones that are of great relevance in the exercise of this modality; since if it is complied In accordance with the provisions of the law, the public sector the assurance that teleworking is a reliable, efficient and suitable way to be exercised, avoiding the disagreement and resistance that several professionals have shown, precisely for the breach of your rights, that is why they prefer to resume their jobs in the traditional way, it should not be the case because they would be against telework, which would be the same as opposing technology, which would be the same as opposing technology, which in addition to being in parmente evolution is part of all human realities, becoming essential its requirement since not only would it be in force until the extinction of the pandemic but it has come to stay, take power in all social, academic, labor, commercial aspects, practically forcing humanity to use it correctly as a basic need.